Language use and preference in the multilingual context of Davao City, Philippines - Jeconiah Louis Dreisbach; Feorillo Petronilo A. Demeterio III (Universitas Syiah Kuala, 2021)
This paper is a pioneering study on the language use and preference of the Davaoeños from generations X (born in the years 1965 to 1979) and Z (born in the years 1995 to 2015) towards the Cebuano, Filipino, and English languages. Being a linguistically diverse area, Davao is home to the emerging contact language Davao Filipino which is currently spoken by the various ethnolinguistic groups currently inhabiting the city. This study utilized mixed methods research, particularly a survey questionnaire and focus group discussions, to explore the perspectives of the respondents on the said languages. Two generations were investigated in this study, particularly those belonging to Generations X and Z. Data presented show that both generations consider themselves fluent in the languages of interest in this study. They primarily use Cebuano for everyday communication and both generations primarily use English in formal communication. However, a language shift was seen from the common use of Cebuano by the older generation to the use of Filipino by the younger generation. This shift was also reflected in the language preferences of the respondents on everyday communication. Lastly, both generations would like to maintain Filipino as the Philippine national language as it is the language that they usually use when talking to Filipinos from other provinces who also speak different Philippine languages.